2021
DOI: 10.1080/21505594.2021.1894834
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic implications of C. albicans-S. aureus mixed biofilm in a murine subcutaneous catheter model of polymicrobial infection

Abstract: Biofilm-associated polymicrobial infections tend to be challenging to treat. Candida albicans and Staphylococcus aureus are leading pathogens due to their ability to form biofilms on medical devices. However, the therapeutic implications of their interactions in a host is largely unexplored. In this study, we used a mouse subcutaneous catheter model for in vivo-grown polymicrobial biofilms to validate our in vitro findings on C. albicans-mediated enhanced S. aureus tolerance to vancomycin in vivo. Comparative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 77 publications
0
36
0
Order By: Relevance
“…is common (Bouza et al, 2013;Kim et al, 2013). Additionally, the combination of both organisms might produce some microbial benefits, as the diffusion of antimicrobial agents through polymicrobial biofilms of Candida and S. epidermidis is slower than the biofilms from each organism resulting an increased drug resistance (Adam et al, 2002;Hall and Mah, 2017;Bernard et al, 2020;Vila et al, 2021). Notably, the antibiotic diffusion through C. tropicalis biofilms is the slowest among all Candida species, indicating a possibility of the unique biofilm structures (AI-Fattani and Douglas, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…is common (Bouza et al, 2013;Kim et al, 2013). Additionally, the combination of both organisms might produce some microbial benefits, as the diffusion of antimicrobial agents through polymicrobial biofilms of Candida and S. epidermidis is slower than the biofilms from each organism resulting an increased drug resistance (Adam et al, 2002;Hall and Mah, 2017;Bernard et al, 2020;Vila et al, 2021). Notably, the antibiotic diffusion through C. tropicalis biofilms is the slowest among all Candida species, indicating a possibility of the unique biofilm structures (AI-Fattani and Douglas, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The second option is in vivo biofilms formed in the host - e.g. mouse and rat catheter models or prosthesis models [48] , [49] , [50] . Various techniques have been used to determine the structure and activity of in vitro biofilms, including microscopic analysis of cell viability, methods to determine biofilm biomass (including the effect of antifungal drugs), often in combination with analysis of specific mutants [15] .…”
Section: Model and Natural Biofilmsmentioning
confidence: 99%
“…C. albicans often forms biofilms in host organisms, along with bacteria such as Klebsiella pneumoniae , Staphylococcus aureus , Streptococcus gordonii , Streptococcus mutans and others, and the coexistence of both organisms often results in the formation of a stronger and more resistant biofilm, compared to single species biofilms [15] , [67] . Omics (especially transcriptomics and proteomics) play an irreplaceable role in revealing the mutual metabolic relationships of microbial species in biofilm and identifying their specific markers ( Table 1 , Table S1) [50] . For example, a recent transcriptomic study revealed the effect of C. albicans on another pathogen, S. aureus , in a mixed-species biofilm formed on a catheter [50] .…”
Section: Model and Natural Biofilmsmentioning
confidence: 99%
See 2 more Smart Citations